Framing cyber warfare : between offence and defence - Chong, Alan (2012)
The increasing frequency of cyber attacks purportedly mounted by state and non-state actors is causing worry worldwide. However policymakers need to steer carefully between their offensive and defensive dimensions in discussing options for cyber defence.